(3OhGFQ geQLs - (3jYbhH Hf ESMGb Hf GdUHGM GdcfOj, CHh jhSa,J (B260 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3Ci acQg ai YXje GdfYeg Ydi GdCeg HNdGag SjOfG CejQ GdeDefjf s
(3BNQgG (B:s
(3bHd GdGfJgGA hCLJgO dCeQ GdBNQI dGjbHd hGddg GYde s
(3cJGH ai CMcGe GdfLhes
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B244s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B209 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B35 s
Keywords: (3Gdadcs